What's in a Name? Reputation as a Tradeable Asset - Tadelis, Steven (American Economic Review, 1999)
I develop a model in which a firm's only asset is its name, which summarizes its reputation, and study the forces that cause names to be valuable, tradeable assets. An adverse selection model in which shifts of ownership are not observable guarantees an active market for names with either finite or infinite horizons. No equilibrium exists in which only good types buy good names. The reputational dynamics that emerge from the model are more realistic than those in standard game-theoretic reputation models, and suggest that adverse selection plays a crucial role in understanding firm reputation. (JEL C70, D80, L14)